Effect of policies directed at youth access to smoking: results from the SimSmoke computer simulation model. Issue 2 (1st June 2001) - Levy, David T; Friend, Karen; Holder, Harold; Carmona, Maria
Abstract : OBJECTIVES: To develop a simulation model to predict the effects of youth access policies on retail compliance, smoking rates, and smoking attributable deaths. METHODS: A model of youth access policies is developed based on empirical research and a theory of perceived risk. The model incorporates substitution into other sources as retail sales are restricted, and is used to project the number of smokers and smoking related deaths. Various policies to limit youth access to cigarettes are evaluated, and we explore how efficient policies may be developed. RESULTS: The model predicts that a well designed and comprehensive policy that includes sufficient compliance checks, penalties, and community involvement has the potential to reduce the number of young smokers. Because smoking related deaths occur later in life, the effects on health are largely delayed. CONCLUSIONS: A well designed youth access policy has the ability to affect youth smoking rates in the short term, and will lead to savings in lives in future years. The ability of retail oriented policies to reduce youth smoking, however, is limited. Other tobacco control policies, including those directed at non-retail sources of cigarettes, are also needed.